The Binocular Advantage in Visuomotor Tasks Involving Tools. (April 2013) - Read, Jenny C. A.; Begum, Shah Farzana; McDonald, Alice; Trowbridge, Jack
We compared performance on three manual-dexterity tasks under monocular and binocular viewing. The tasks were the standard Morrisby Fine Dexterity Test, using forceps to manipulate the items, a modified version of the Morrisby test using fingers, and a "buzz-wire" task in which subjects had to guide a wire hoop around a 3D track without bringing the hoop into contact with the track. In all three tasks, performance was better for binocular viewing. The extent of the binocular advantage in individuals did not correlate significantly with their stereoacuity measured on the Randot test. However, the extent of the binocular advantage depended strongly on the task. It was weak when fingers were used on the Morrisby task, stronger with forceps, and extremely strong on the buzz-wire task (fivefold increase in error rate with monocular viewing). We suggest that the 3D buzz-wire game is particularly suitable for assessing binocularly based dexterity.